Addressing the Anxiety Surrounding Loans and Mitigating Capital Deficiencies for MSME Advancement - Jumriah Basri; Suriadi Suriadi; Amrizal Salida; Yahya Yahya; A. Kartini Sari Putri D (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
The critical role of Micro, Small, and Medium Enterprises (MSMEs) in driving economic growth and fostering social stability is well-recognized globally. These enterprises are the backbone of economies, contributing significantly to employment creation, innovation, and equitable income distribution. However, despite their potential, MSMEs face persistent challenges that hinder their growth and sustainability, with access to capital and loan-related anxieties standing out as primary barriers. This study aims to identify the factors that cause anxiety of Micro, Small, and Medium Enterprises (MSME) about capital loans and develop strategies to mitigate capital shortages to encourage the progress of MSMEs. This research employed a qualitative approach involving in-depth interviews with ten microenterprise actors engaged in beverage sales in Pangkajenne City. The participants were selected based on specific criteria: they had been operating for a minimum of one year, offered a diverse range of beverage products, and reported experiencing anxiety related to the need for capital. Research has found that loan-related anxiety is mainly caused by uncertainty of returns, ignorance of loan terms, and social stigma related to default. On the other hand, mitigation strategies such as financial literacy training, simplification of the loan application process, and access to flexible microfinance schemes have proven effective in reducing the concerns of MSME actors. This study was limited to a sample of MSMEs in specific regions and did not cover all business sectors. In addition, this study must discuss in depth the influence of macroeconomic factors on MSME capital access. This research provides valuable insights into the relationship between loan anxiety and capital shortages and offers relevant mitigation strategies. The results of this study enrich the literature on MSME financial management, especially in the context of developing countries. This study combines the perspectives of MSME actors and financial service providers to understand the dynamics of loan-related anxiety, which has been previously underexplored in the literature.